Rancangan Sistem Pendukung Keputusan “TechTrack” Berdasarkan Evaluasi Kualitas UI/UX Aplikasi - Made Bayu Maha Krisna Siaka; I Gede Arta Wibawa (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
Smartphone is a portable electronic communication device that enables individuals to engage in various activities, including work, communication, and entertainment. It serves as a versatile tool that can be easily carried and utilized in different locations, providing convenience and facilitating human interactions across multiple domains.